ANALISIS PENINGKATAN STATUS HAK DARI HAK PAKAI YANG TERIKAT JAMINAN DI ATAS HAK PENGELOLAAN MENJADI HAK MILIK - MUHLIS FAHDIAR SEMBIRING (PREMISE LAW JURNAL, 2014)
ABSTRACT Based on the result of the research, it can be concluded that with the registration of the land rights by individuals and by legal entity legally, and the publication of land certificates, the government will guarantee the security of the land ownership. In order to be used optimally and to fulfill the public need for land, the government has applied one of the philosophical elements of the Agrarian Law that says: “the National Agrarian Law should provide the possibility for the realization of the functions of land, water, and air for the benefit of the Indonesian people and should be appropriate for the progress of time in the agrarian problems.” This statement becomes the reason for the request for the land rights (escalation process). The legal problem of the escalation status of the right of use of the guarantee from the cultivating right to the property right is the lack of information about the benefit of the escalation of the rights, the lack of education and knowledge of the people, and the incompleteness of dossier to fulfill the administrative requirements in the process of the escalation of the rights. Keywords: Escalation the Right Status, Right of Use, Hypothecation, Right of Cultivation, Property Rights